PERANCANGAN DAN PEMBUATAN PURWARUPA PENDETEKSI SUHU TUBUH DAN SANITASI TANGAN TANPA SENTUHAN - Mochammad Safarudin; Diki Maulana (Sekolah Tinggi Teknologi Mandala Bandung, 2022)
The corona virus (Covid-19) has hit almost the whole world, including Indonesia. Community activities must comply with health protocols, one of which is checking human body temperature. Body temperature measurement sensors are very significant differences even though they are applied to the same human body, this is caused by several factors. In this design, it provides the results of detecting the use of masks that are used before using health protocol tools. The mask detection process uses a web camera that is integrated with a Python script code program to interact with the algorithm to be designed. This design provides the measurement results of the human body temperature sensor. This design aims to find out an effective and efficient health protocol for humans. The process of measuring human body temperature using a microcontroller-based temperature sensor. After obtaining the results of measuring body temperature using a temperature sensor, the measurement results are used as a lighter to run a microcontroller-based health protocol system as well. The system applied is the development of a manual hand sanitization health protocol implementation mechanism. After obtaining the results of the permissible body temperature using a body temperature detection sensor, the measurement results are directed to run a hand sanitation system. In order to obtain an effective and efficient hand sanitation system. The level of effectiveness of health protocols affects the continuity of activities. The higher the level of effectiveness, the faster the process of checking health protocols will be carried out. In addition, the use of this tool is expected to provide convenience in implementing health protocols.